2011
DOI: 10.1111/j.2041-1626.2011.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Actual proliferating index in oral squamous cell carcinoma and leukoplakia

Abstract: Leukoplakia or suspected epithelial dysplasia should be stained for argyrophilic nucleolar organizer regions and Ki-67. The actual proliferation index is not only useful as a prognostic factor, but could also be a promising treatment determining modality for patients with premalignant and malignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The median Ki-67 LI increased from keratosis without dysplasia to keratosis with dysplasia to OSCC in this study, and the relationship was statistically significant. As noted in this study, similar findings were observed in the studies performed by Iamaroon et al 16 , Dwivedi N et al 10 , Santos-Garcia A et al 17 and Dragomir LP et al 24 The median Ki-67 LI was also higher in keratosis with dysplasia than keratosis without dysplasia, concurrent with the findings by Kurokawa H et al 9 and Chandak AR et al 25 The increase in number of Ki-67 positive cells with the increase in histological grades of OSCC from WDSCC to MDSCC to PDSCC has been highlighted by various authors Ashraf MJ 7 , Verma R 20 , Dwivedi N et al 10 and Chandak AR et al 25 Moreover the studies done by Motta R et al 21 and Thomson PJ et al 23 have shown highest Ki-67 immunoexpression in lesion with cervical metastasis. The importance of Ki-67 overexpression in atypical oral epithelium and its association with recurrence/malignant transformation, independently of other established clinicopathological factors including age, lesion site, epithelial dysplasia has been highlighted by Yagyuu T et al in their study.…”
Section: Discussionsupporting
confidence: 91%
“…The median Ki-67 LI increased from keratosis without dysplasia to keratosis with dysplasia to OSCC in this study, and the relationship was statistically significant. As noted in this study, similar findings were observed in the studies performed by Iamaroon et al 16 , Dwivedi N et al 10 , Santos-Garcia A et al 17 and Dragomir LP et al 24 The median Ki-67 LI was also higher in keratosis with dysplasia than keratosis without dysplasia, concurrent with the findings by Kurokawa H et al 9 and Chandak AR et al 25 The increase in number of Ki-67 positive cells with the increase in histological grades of OSCC from WDSCC to MDSCC to PDSCC has been highlighted by various authors Ashraf MJ 7 , Verma R 20 , Dwivedi N et al 10 and Chandak AR et al 25 Moreover the studies done by Motta R et al 21 and Thomson PJ et al 23 have shown highest Ki-67 immunoexpression in lesion with cervical metastasis. The importance of Ki-67 overexpression in atypical oral epithelium and its association with recurrence/malignant transformation, independently of other established clinicopathological factors including age, lesion site, epithelial dysplasia has been highlighted by Yagyuu T et al in their study.…”
Section: Discussionsupporting
confidence: 91%
“…cases with negative margins developed a recurrence as compared t1 (30.4%) cases with close margins and 42.8%) cases with positive margins. According to Chandak et al [5] API in normal mucosa was found to be 7.41, in Leukoplakia -52.51. In OSCC-180.9.…”
Section: Discussionmentioning
confidence: 91%
“…API can distinguish between dysplastic and nondysplastic leukoplakia. So, it can be useful to evaluate dysplasia in surgical margins [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral squamous cell carcinoma (OSCC) is one of the top ten cancers in the world,[ 2 ] ranks first among males and third among females in India. [ 3 ] Regardless of advanced diagnosis and treatment modalities, it carries potentially poor prognosis with an estimated survival rate of only 56%. [ 4 ] Prognosis of OSCC is intimately related to nodal metastasis.…”
Section: Introductionmentioning
confidence: 99%